Crosstalk of dynamic functional modules in lung development of rhesus macaques. Issue 4 (29th February 2016) - Yu, Xuexin; Feng, Lin; Han, Zujing; Wu, Bo; Wang, Shuyuan; Xiao, Yun; Li, Feng; Zhang, Lianfeng; Cao, Bangrong; Di, Xuebing; Lu, Dan; Li, Xia; et al.
Abstract : Our study presents the landscape of gene expression of lung development of rhesus macaques, and provides an extended insight into the lung development mechanism. Abstract : Lung development follows a complex series of dynamic histogenic events that depend on the fluctuation of gene expression, and the disruption of gene regulation could lead to devastating consequences, such as diseases in adulthood. In order to investigate the mechanism of lung development, we performed RNA sequencing by Illumina HiSeq™ 2000 to measure mRNA expression in lung tissues of nine rhesus macaques spanning from foetuses at gestation of 45 days to postnatal at 7 days. This development period was divided into three developmental stages, including the early stage (45–100 gestational days), the middle stage (137–163 gestational days) and the late stage (after birth at 4–7 days). Firstly, we identified stage-specific genes, based on which we found that the principle biological processes of the early stage were mainly associated with internal growth signalling, while the middle and late stage-specific genes controlled the external stress signalling. Then, we constructed a stage-specific protein–protein interaction (PPI) subnetwork, extracted dynamic modules, and identified crosstalk between modules. Moreover, we found four active pathways that could mediate the crosstalk, including the Notch signalling pathway, cell cycle, NOD-like receptor signalling pathway, and Toll-like receptor signalling pathway. These pathways not only played crucial roles in lung development, but also were implicated in lung diseases. Finally, some important bridgers, such as PSEN2, HSP90AA1 and CASP8, were discovered to explain the potential mechanism of crosstalk. Therefore, our study presents the landscape of gene expression of lung development of rhesus macaques, and provides an extended insight into the lung development mechanism.